THE APPLICATION OF DRTA (DIRECTED READING THINKING ACTIVITY) TO IMPROVE READING COMPREHENSION OF SECOND GRADE STUDENTS OF SMK MUHAMMADIYAH 2 PEKANBARU - Syatra Safira Anjani Safira Anjani; Jismulatif '; Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This was a Classroom Action Research. This research was about the application of DRTA (Directed Reading Thinking Activity) to improve reading comprehension. The objective was to improve the ability of the second grade students of SMK Muhammdiyah 2 Pekanbaru in reading comprehension by using DRTA strategy. It was conducted to the second grade students of SMK Muhammadiyah 2 pekanbaru especially XI AK 2 as the subject of research. Reading comprehension test and observation sheet were used as the tools of collecting the data. The result of this research showed that DRTA strategy could improve the students’ ability in comprehending reading texts. Students’ mean score improved from 46.62 in pre-test to 63.39 in post-test 1, and to 79.19 in post test 2. It is in line with the activeness of students that improved from post test 1 to post test 2. The students were able to identify the main idea, references, and supporting idea of the text. DRTA strategy could improve the students’ prior knowledge by predicting the text and confirm or revise their prediction. This research recommended that teacher could use DRTA strategy to improve students’ ability in reading comprehension since it was an effective strategy by predicting the text and then confirm or reject their prediction.Key words: DRTA (Directed Reading Thinking Activity) strategy, reading comprehension